Preparation of magnetic biochar obtained from one-step pyrolysis of salix mongolica and investigation into adsorption behavior of sulfadimidine sodium and norfloxacin in aqueous solution. Issue 2 (28th January 2020) - Liu, Penglei; Li, Hongping; Liu, Xiao; Wan, Yibei; Han, Xiuli; Zou, Weihua
Abstract: In this work, salix mongolica, pretreated by FeCl3 and ZnCl2, was applied as a precursor to prepare the magnetic biochar (MBC, containing γ-Fe2 O3 ) with the method of one-step pyrolysis. According to the characterization results of MBC (SEM, XPS, XRD, FTIR, VSM, BET), the features of biochar and the magnetic properties of iron oxides were combined in a composite of MBC. The magnetic biochar can be used as adsorbent for sulfadimidine sodium (SMS) and norfloxacin (NOR) removal from aqueous solution and subsequently removed from the medium by a simple magnetic process. The adsorption characteristics of SMS and NOR from aqueous solution by MBC have been investigated. The adsorption kinetics was best described by Elovich model. The equilibrium data was best fitted by the Freundlich isotherm and Koble-Corrigan model implying the adsorption process mainly was multilayer adsorption on heterogeneous surfaces. The maximum adsorption capacity for SMS and NOR was 251 mg/g and 210 mg/g at 308 K, respectively. The values of thermodynamic parameters were calculated indicating the process of adsorption was an endothermic and spontaneous process. The adsorption mechanism may be attributed to the π–π dispersion, the hydrophobic interaction, hydrogen bonding or the electrostatic interaction between the MBC and the molecule of NOR or SMS. GRAPHICAL ABSTRACT: